THE MOON: A TAYLOR PERSPECTIVE - Taylor S.R.; Taylor G.J.; Taylor L.A. (My University, 2006)
We address several current lunar problems. The data suggest that the Moon likely possesses an Fe-rich metallic core a few percent of lunar volume, although definitive proof is lacking. Refractory elements appear to be enriched relative both to the composition of the primordial solar nebula (CI) and the Earth. Very volatile elements appear to be depleted uniformly at high levels. We adopt the single-impact hypothesis for lunar origin, which formed a high-temperature silicate vapor disk, mostly of metal-poor silicate material from an impactor (Theia) that was already depleted in volatiles. We speculate that the curious lunar bulk-composition resulted from condensation from high-temperature vapor at around a few Earth radii. This could produce an enriched refractory-element composition that cut off below 1000 K, producing a uniform depletion in very volatile elements. © 2006.